2012
DOI: 10.1002/ece3.356
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects between diet and genotypes of host and pathogen define the severity of infection

Abstract: Host resistance and parasite virulence are influenced by multiple interacting factors in complex natural communities. Yet, these interactive effects are seldom studied concurrently, resulting in poor understanding of host-pathogen-environment dynamics. Here, we investigated how the level of opportunist pathogen virulence, strength of host immunity and the host condition manipulated via diet affect the survival of wood tiger moth Parasemia plantaginis (Arctidae). Larvae from “low cuticular melanin” and “high cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…; Zhang et al. ) favors more melanic coloration with less conspicuous, and smaller sized, bright patterns. In addition, the strength and direction of selection on the warning signal traits can vary both spatially (Lindstedt et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zhang et al. ) favors more melanic coloration with less conspicuous, and smaller sized, bright patterns. In addition, the strength and direction of selection on the warning signal traits can vary both spatially (Lindstedt et al.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the trade-off between larval and female warning signal efficiency can be strongly dependent on the spatial and temporal variation in the direction and strength of selection. Previous studies have shown that warning coloration of larvae and adults of A. plantaginis are under multiple selection pressures, as predation favors an increase in size and conspicuousness of brightly colored pattern elements (Lindstedt et al 2008(Lindstedt et al , 2011Nokelainen et al 2012) while thermoregulation Hegna et al 2013) and defense against pathogens (Friman et al 2009;Zhang et al 2012) favors more melanic coloration with less conspicuous, and smaller sized, bright patterns. In addition, the strength and direction of selection on the warning signal traits can vary both spatially (Lindstedt et al 2011;Nokelainen et al 2014;Gordon et al 2015) and seasonally ) in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, we can assume that in environments of high predation pressure, directional selection by predators should favour larger (Hegna, Nokelainen, Hegna, & Mappes, 2013;Lindstedt et al, 2008) and more salient (Lindstedt et al, 2011;Nokelainen, Hegna, Reudler, Lindstedt, & Mappes, 2012) warning signals in both the larval and adult stages of A. plantaginis and thus by default, less melanization surrounding them. However, in colder habitats (Hegna et al, 2013;Lindstedt et al, 2009), under higher risk of bacterial infections (Friman, Lindstedt, Hiltunen, Laakso, & Mappes, 2009;Zhang, Friman, Laakso, & Mappes, 2012), and under higher abundances of naïve predators (Lindstedt et al, 2008;Mappes, Kokko, Ojala, & Lindström, 2014), more melanic (i.e. more cryptic) genotypes should have an advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating resilience in insect midguts have shown that these communities are able to return to native community structure once removing perturbation factors such as antibiotics or high fat concentrations [17] [32]. In this study, the perturbation factor was not removed and yet the sinigrin 9.0 mg/ml treatment group showed no significant difference from the control treatment group.…”
Section: Discussionmentioning
confidence: 68%